Thai patients who fulfilled NCCN criteria for breast/ovarian cancer genetic assessment demonstrated high prevalence of germline mutations in cancer susceptibility genes: implication to Asian population testing - Lertwilaiwittaya, Pongtawat (Breast Cancer Res Treat, 2021)
BACKGROUND: Germline genetic mutation plays a significant role in breast cancer susceptibility. The strength of such predisposition varies among ethnic groups across the globe, and clinical data from Asian population to develop a strategic approach to who should undergo a genetic test are lacking. METHODS: We performed a multigene test with next generation sequencing in Thai patients whose clinical history fulfilled NCCN criteria for breast/ovarian cancer genetic assessment, consists of 306 breast cancer patients, 62 ovarian cancer patients, 14 pancreatic cancer patients and 7 prostate cancer patients. Genetic test result and clinical history were then checked with each NCCN criteria to determined detection rate for each indication. RESULTS: There were 83 pathogenic/likely pathogenic (P/LP) variants identified in 104 patients, 44 of these P/LP variants were novel. We reported a high rate of germline P/LP variants in breast cancer (24%), ovarian cancer (37%), pancreatic cancer (14%), and prostate cancer (29%). Germline P/LP variants in BRCA1 and BRCA2 accounted for 80% of P/LP variants found in breast cancer and 57% of P/LP variants found in ovarian cancer. The detection rate of patients who fulfilled NCCN 2019 guideline for genetic/familial high-risk assessment of breast and ovarian cancers was 22–40%. CONCLUSION: Overall, the data from this study strongly support the consideration of multigene panel test as a diagnostic tool for patients with inherited cancer susceptibility in Thailand and Asian population. Implementation of the NCCN guideline is applicable, some modification may be needed to be more suitable for Asian population.